Pertumbuhan dan Hasil Dua Klon Ubijalar dalam Tumpang Sari dengan Jagung - Suwarto, Suwarto; Setiawan, Asep; Septariasari, Dina (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
An experiment to evaluate the growth and yield of two sweetpotato clones in intercropping with maize was conducted in IPB experimental farm in Sawah Baru from December 2004 to April 2005. In intercropping, the two sweetpotato clones of CIP-1 and CIP-6 were planted among to maize rows.  Planting space of sweet potato was 100 cm x 25 cm and maize was 100 cm x 12.5 cm in a plot size of 3 m x 3 m. Besides, the two crops were also planted in monoculture. The experiment was designed as a Randomized Block Design (RBD) and replicated three times. Dry matter of stem, leaves, and roots of the two sweet potato clones in intercropping were lower than in monoculture.  The same response occurred for yield of storage root.  The storage root weight of sweet potato clone, respectively, in monoculture and intercropping was 1.350 and 2.533 kg plot-1 of CIP-1 and 3.167 and 11.083 kg plot-1 of CIP-6.  On the other hand, there was no significance difference in growth and yield of maize in monoculture (3.35 kg plot-1) and intercropping (3.13 kg plot-1).  Land equivalent ratio of the intercropping maize with CIP-1 and CIP-6 were 1.7 and 1.4, respectively.  It means that land productivity can be increased by those intercropping.   Key words: Sweet potato clones, intercropping, maize